Description of ticks species from Rattus tiomanicus in Mangrove Forests through scanning electron microscopy - Asyikha, Rosha; Mohd-Taib, Farah Shafawati; Nabilah Ishak, Siti; Jing Jing, Khoo; Sulaiman, Norela (Systematic and applied acarology, 2022)
Ticks are ill-famed vectors of many pathogenic organisms which can cause various diseases and life-threatening illnesses to animals and humans. Each tick’s species and its life stages have distinct morphological features that can permit them to be accurately identified. However, the use of conventional stereo microscopes limits the accuracy of species identification. The taxonomy of ticks, in general, is not much understood and existing information is based on sparse morphology data. Thus, this study aims to examine and describe the morphological characteristics of different species of ticks collected on rodents in mangrove forests using scanning electron microscopy (SEM). This method renders high-quality images of body parts of ticks. Five different morphospecies of ticks from one host species (Rattus tiomanicus) were examined under SEM, followed by the PCR technique using mitochondrial 16S rDNA gene for species validation. This study revealed that the ticks belong to five species: Dermacentor auratus, Ixodes granulatus, Haemaphysalis hystricis, D. atrosignatus and Amblyomma cordiferum. The combination of stereomicroscopic and SEM methods has improved our understanding of the morphological characteristics of different tick species, hence establishing up-to-date taxonomic keys for these species. Moreover, due to the lack of taxonomic keys on the immature stage of ticks, the SEM method is essential in characterising the morphological features of these stages in detail, subsequently helpful in revising the taxonomic keys for certain ticks species.